MORPHOLOGICAL ANALYSIS OF THE LITERARY TEXT OF TERE LIYE’S RAIN NOVEL - Alfianita, Alfianita; Habiba Tsalisa Shofiah; Mikail Randu Rayyana; Endang Sholihatin (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
In the novel Hujan, Tere Liye uses various forms of morphology to form new words. The use of morphology makes the novel richer and more diverse. In addition, the use of morphology also helps Tere Liye convey his messages more effectively. The novel has interesting themes, which are about love, life struggles, and natural disasters. These themes are universal and can be accepted by everyone. Author Tere Liye is a well-known writer whose works are always bestsellers in the market. He has a beautiful and easy-to-understand language style. The language style of this novel has a beautiful and poetic language style. This language style makes the novel more interesting and easy to understand. The theme of love and life struggle raised in this novel also uses Tere Liye's poetic and meaningful language style. In addition, researchers also want to know how the love story of Lail and Rangga is hindered by differences in the future. Knowing the morphological analysis of word change and formation in Tere Liye's Rain Novel. Knowing the morphological analysis on word reduplication in the novel Rain by Tere Liye. Knowing the morphological analysis on word compounding in the novel Rain by Tere Liye. The research method used is the descriptive qualitative method through literature study. The theory used to analyze the data is Chaer's theory. To collect data, the method used is the listening method with a high note-taking technique, while to analyze the data the author uses the high method with the direct element dividing technique (BUL). Based on the results of the research, five forms of affixation were found in the novel Hujan by Tere Liye, namely (1) prefixes (ber-, me-, pe-, ter-, and di-), (2) suffixes, (-an, -kan, and -i), (3) infixes, (-em-) (4) confixes, (ke-an, pe-an, per-an, me-kan, per-kan, and member-i), and (5) clofixes. (ke-an, pean, per-an, ber-an, me-kan, per-kan, ber-kan, di-i, me-i, and per-i). In the morphological analysis of the novel "Rain" by Tere Liye, it can be concluded that; Morphology can bring word changes in the novel Rain by Tere Liye. Morphology can reduplicate words in the novel Rain by Tere Liye. Morphology can be analyzed through word compounding in Tere Liye's novel Rain. In addition, Tere Liye also uses changes in word forms through reduplication or repetition of words to provide emphasis or certain rhetorical effects. The use of reduplication also gives a strong emotional impression on the reader. Overall, the analysis of morphology in the novel "Rain" by Tere Liye shows that the use of morphological variations can enrich the language and give uniqueness to literary works.